UV curable sulfonated hybrid materials and their performance as proton exchange membranes - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER, 2009)
In this study 2-acrylamido-2-methylpropanesulfonic acid (AMPS) containing UV curable nanocomposite membranes were prepared by using the sol-gel method. Tetraethylorthosilicate (TEOS), and 3-(methacryloyloxy)propyl trimethoxysilane (MAPTMS) were used, respectively as an inorganic precursor and coupling agent. Cross linking agents such as poly(ethylene glycol diacrylate) (PEGMA) and ethylene glycol dimethacrylate (EGDMA) were used to arrange the mechanical and physical properties of the resulting hybrid membrane. The hybrid formulation polymerized under UV irradiation and the gel percentage, water uptake of the membranes were calculated. The polymerization conversion of the organic part was investigated by using photo-differential scanning calorimetry (photo-DSC). The thermal and mechanical properties of the membranes indicated good stability. The morphological structure of membranes was investigated by scanning electron microscopy (SEM). In addition proton conductivity and methanol selectivity measurements were performed. The proton conductivity of the AMPS20-SOLGEL30 nanocomposite membrane is about 0.138 S cm(-1) at 50 degrees C. Selectivity toward methanol for the same membrane is very low with a selectivity factor of alpha = 0.032, which satisfies the requirements for DMFC applications. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Sol-gel; 2-Acrylamido-2-methyl propane sulfonic acid; UV-curing; Proton conductivity; Fuel cell; COMPOSITE ELECTROLYTE MEMBRANE; ACID; CONDUCTIVITY; SILICA; POLYMERIZATION; COPOLYMER; HYDROGELS